MEMPERKUAT FORUM KERUKUNAN UMAT BERAGAMA (FKUB) - Husni Mubarok (Jurnal Dialog, 2014)
This paper discusses the strategic position of FKUB (Communication Forum of Inter-Religious Communities) for the future of inter-religious harmony in Indonesia, particularly the freedom of religion. It also highlights some issues that might disempower this inter-faith organization. Finally, this paper proposes some ideas for empowering FKUB by listing its weaknesses and some alternative solutions.